Brahman Cross (BX) Quality of Spermatozoa From Sex Results with Different Temperatures - Astuti, Meri; Saili, Takdir; Aku, Achmad Selamet; Nafiu, La Ode (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2024)
This study investigates the influence of varying temperatures on sexed spermatozoa and its impact on the quality of Brahman cross (Bx) cattle sperm. The research was carried out at the Animal Breeding and Animal Feed Center in Southeast Sulawesi Province, utilizing spermatozoa from Brahman cross (Bx) bulls. Using a Completely Randomized Design with three treatments (temperatures) - P1 (29°C), P2 (21°C), and P3 (37°C), each with a sexing time of 20 minutes - the study assessed macroscopic and microscopic aspects of fresh spermatozoa. Key parameters included volume, color, pH, concentration, viability, and motility percentage. Statistical analyses revealed significant effects of different sexing temperatures (P